UPAYA MENINGKATKAN PRESTASI BELAJAR IPS DAN KETERAMPILAN SOSIAL SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) PADA SISWA KELAS IV SDN TERBAN BAMBANGLIPURO BANTUL - Deni P, Heni Sinta (Jurnal PGSD Indonesia, 2015)
AbstrakPenelitian ini bertujuan untuk mengetahui upaya meningkatkan prestasi belajar IPS dan keterampilan sosial siswa dengan model pembelajaran kooperatif learning tipe Student Teams Achievement Divisions (STAD) pada siswa kelas IV SDN Terban Bambanglipuro Bantul. Hasil penelitian menunjukkan bahwa nilai rata-rata prestasi belajar pra siklus 68 dengan persentase ketuntasan 40% dan keterampilan sosial 64,5 dengan persentase 40%, siklus I nilai rata-rata prestasi belajar 71 dengan persentase ketuntasan 70% dan persentase keterampilan sosial siswa pada pra siklus sebesar 40% berada kategori cukup, siklus I persentase sebesar 70% berada kategori cukup dan siklus II persentasenya 90% masuk kategori baik. Kesimpulan hasil penelitian ini yaitu bahwa model pembelajaran Kooperatif Learning Tipe Student Teams Achievement Divisions (STAD) dapat meningkatkan prestasi belajar dan keterampilan sosial siswa kelas IV SDN Terban Bambanglipuro Bantul.Kata kunci : Prestasi belajar, IPS, Keterampilan sosial, Student Teams Achievement Divisions (STAD)AbstractThis study aim to determine the efforts to improve social science learning achievement and students social skills with cooperative learning model of type Student Teams Achievement Divisions (STAD) in the fourth grade students of Terban Elementary School Bambanglipuro Bantul. This type of research is classroom action research which consists of four stages: planning, implementation, observation and reflection. The subjects are 10 students. Data collection technique used tests, observation, documentation and field notes. This research is conducted in collaboration with classroom teachers so that researchers directly involved in the research process from beginning to the end. Indicators of success in learning achievement is marked by the increasing of social studies by 75% and the social skills of students successfully if 80% of students are belongs to the good category. The data analysis technique used in this research by calculating the average score and the percentage of mastery learning. The results of this study is concluded that STAD learning model can improve the learning achievement and social skills of the fourth grade students. The results showed that the average score of the learning achievement of pre cycle 68 to 40% the percentage of completeness and social skills with a 64.5 percentage of 40%, the first cycle of the average score of learning achievement completeness 71 with a percentage of 70% and the average score of social skills 68 to 70% the percentage of completeness in the middle category, on the second cycle the average score of learning achievement with a percentage of 79.5 completeness 90% while the average score of social skills with a percentage of 76.5 completeness 90% in the good category.Keywords: Academic Achievement, Social Studies, Social Skills, Student Teams